Delirium incidence, risk factors, and treatments in older adults receiving chemotherapy: A systematic review and meta-analysis. Issue 3 (April 2021) - Jung, Patrick; Puts, Martine; Frankel, Nelly; Syed, Ali Taqi; Alam, Zuhair; Yeung, Lily; Malik, Uzair; Rosario, Carla; Ayala, Ana Patricia; Hudson, Julie; Alibhai, Shabbir M.H.
Abstract: Introduction: Older adults with cancer are at increased risk of delirium due to age, comorbidities, medications, cognitive impairment, and possibly cancer treatments. However, there is scant information on the risks of delirium with chemotherapy and approaches to prevent or treat it. We performed a systematic review and meta-analysis to summarize available evidence. Materials and Methods: We systematically searched peer-reviewed journal articles in English, French, German, and Dutch from five databases from 1990 to May 2019 to identify studies examining delirium in adult patients receiving chemotherapy. We also attempted to identify delirium risk prediction models and prevention or treatment trials. All reviews and data extraction were performed by two independent reviewers. Summary estimates were derived from random effects models. Results: A total of 23, 389 titles and abstracts were screened, and 1272 full-text articles were reviewed. Nineteen articles reported on delirium using an acceptable diagnostic standard. Sample sizes varied from 7 to 324. The incidence of delirium ranged from 0 to 51% (weighted mean 9%, 95% confidence interval 5–16%). In a sensitivity analysis including 122 studies that used terminology suggestive of delirium but did not meet our inclusion criteria, the weighted incidence of delirium was 10% (95% confidence interval 8–12%). Age was not consistently associated with increased delirium risk. No intervention studies to prevent or treat delirium were identified. Conclusions: Delirium may occur in 1 in 11 older adults receiving chemotherapy; however, there were substantial limitations in reported studies. This systemic review highlights key gaps in knowledge, particularly regarding risk factors, prevention, and treatments.